Pré-natal e morbidade materna em populações dos campos, das florestas e das águas em Altamira-PA - LOURINHO, Gisele Silva (2023)
Introduction: Prenatal care aims to follow a woman since the beginning of her pregnancy and, for that reason, to provide a greater attention to those with risk factors for an unfavorable evolution and/or outcomes. In this context, this work consisted in an analysis of the relation between those outcomes with the access and quality of prenatal care carried out by women members of the Populations of Fields, Forests and Waters (PCFA) in the municipality of Altamira-PA. Objective: To evaluate the access and quality of PCFA prenatal care and its relationship with maternal morbidity in the pregnancy-puerperal cycle. Methodology: Field study, analytical and prospective, with a quantitative approach. Participated in the research: women during pregnancy, childbirth or immediate postpartum included in the classification of the National Policy for Comprehensive Health of Populations of Fields, Forests and Waters (PNSIPCFA) and admitted to the General Hospital of Altamira (HGA). In the established period, data collection took place in three stages: interview with the woman in the immediate postpartum period, through a structured questionnaire prepared by the authors and analysis of the Pregnant Woman's Handbook; health promotion through guidance and analysis of the medical records of the interviewed patients, in which the complications during pregnancy, childbirth and immediate postpartum focused in the study were verified, using the classification of "ICD-10, Chapter XV: pregnancy, childbirth and puerperium”. For data analysis, we used the chi-square likelihood ratio test for independent samples, Microsoft Excel and Statistic Package for Social Sciences (SPSS) version 24.0, all in Windows 7 environment. This research was approved by the Ethics Committee for Research with Human Beings at the Federal University of Santa Catarina (CAAE 283114200.6.0000.0121). Results: The coverage and quality of prenatal care in PCFA is still unsatisfactory, as most respondents started prenatal care after the 12th week (56.7%) and had less than six appointments (56 .7%). They pointed as the main reasons for that: the long distance to the health center (50%), the financial cost of this travel (30%) and the fear of coronavirus pandemic. Another way to assess the quality of prenatal care is the clinical procedures, alongside with laboratory and imaging tests, which had low adherence by most postpartum women. Discussion: Regarding the correlation of prenatal deficiency and the occurrence of negative outcomes, the research found relevant results, even with the small sample and the absence of information records. Conclusion: Government actions must consider the specificities of these groups, as well as invest in the health decentralization process in Brazilian municipalities, ensuring citizens the right to integral health. Therefore, the importance of this work is to bring greater visibility to the theme, to contribute to the transformation of this reality in Altamira, in addition to enrich studies at a national level.